Excited state dynamics in SO2: III. An "ab initio" quantum study of single- and multi-photon ionization - Lévêque, Camille; Köppel, Horst; Taïeb, Richard (The journal of chemical physics, 2014)
We present an ab initio quantum study of the photoelectron spectra of sulfur dioxide, based on wavepacket propagations on manifolds of ionic, and excited/Rydberg states. We obtain excellent agreement for two different cases. First, the one photon ionization case where we can reproduce all details of the experimental spectrum and demonstrate the influence of the conical intersection between two of the ionic states. Then the multiphoton ionization regime, in which the dynamics of the wave packet on the two lowest singlet states is directly mapped in the spectra via a pump-probe scheme, as proposed in the experimental companion paper [I. Wilkinson et al., J. Chem. Phys. 140, 204301 (2014)].
Im Titel ist "2" tiefgestellt
Gesehen am 29.07.2020